(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
Studies have been conducted of the influence of nanocarbon materials on the structure and some physical properties of amorphous and crystalline polymers. It has been shown that an increase in filler content in polymers is accompanied by changes in structure, mechanical and thermal properties. The formation of crystal solvates in the ternary polymer-fullerene-solvent system in crystalline polymers and the formation of superstructures-spherulites in amorphous polymers were discovered. The observed changes are explained in terms of the competing influence of the interaction of the polymer with fullerene and solvent, changes in the state of the amorphous regions of the polymer upon introduction of the filler, and the technology for producing nanocomposites.